О сходимости схемы метода конечных элементов для уравнения внутренних волн - Москальков, М.Н.; Утебаев, Д. (Кибернетика и системный анализ, 2011)
Розглянуто першу крайову задачу для рівняння внутрішніх хвиль. Для її розв’язання вибрано метод скінченних елементів як за просторовими змінними, так і за часом. Це дозволяє одержати розв’язок підвищеної точності. Отримано оцінки точності методу при відповідних припущеннях про гладкість розв’язків диференціальної задачі. При використанні кусково-кубічних елементів порядок точності дорівнює трьом. This work considers the first extreme problem for the equation of internal waves. To solve it, the finite element method is selected for spatial variables and time. This allows one to obtain a solution of extended precision. Accuracy estimates are obtained for schemes of the method under appropriate assumptions on the smoothness of solutions to the differential problem. In using piecewise-cubic finite elements, the accuracy degree equals three.